A Clinical Case of a 10-Month-Old Child with Severe COVID-19 with Multisystem Inflammatory Syndrome Ended Fatally - Parusheva P.; Pekova L.; Angelova S. (Acta Medica Bulgarica)
At the beginning of the COVID-19 pandemic, it was assumed that children were at low risk of infection and that their infection was milder than adults. With an increase in the number of pediatric cases of SARS-CoV-2 infection associated with manifestations of hyperinflammation, the condition of multisystem inflammatory syndrome in children (MIS-C) was defined. We present a clinical case of a 10-month-old male child hospitalized in the Clinic of Infectious Diseases at University Hospital in Stara Zagora, Bulgaria, with a COVID-19. The patient had a number of co-morbidities, including protein-calorie malnutrition, chronic respiratory failure and bronchopulmonary dysplasia. During the hospital stay, he had an active diarrhea syndrome, with evidence of pneumonia and respiratory failure. In the clinical course, a progressive worsening of the condition with signs of multiple organ failure, increase in inflammatory markers and deterioration of coagulation indicators were observed. Placement in the ICU and the inclusion of artificial pulmonary ventilation were required, but after an 18-day hospital stay, the patient died. In conclusion, this was an acute case of COVID-19 in an infant that started with respiratory and gastrointestinal manifestations that progressed to MIS-C with multiple organ failure leading to death. We believe that the reason for this is the compromised immune status in connection with the highly damaged premorbid terrain and young age.